Desain modul matematika pendamping untuk persiapan asesmen kompetensi minimum Siswa Kelas V SD - Heru, Heru; Yuliani, Refi Elfira; Zulpah, Izah (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2022)
Students' skills in solving numeracy questions in the AKM are still varied, especially for SD Negeri 3 Mendo Barat students. The implementation of AKM, especially numeracy skills, impacts the learning given to students. Students are not only required to understand mathematical concepts but must demonstrate other mathematical abilities such as reasoning and problem-solving abilities. Therefore, teaching materials are needed that can support the AKM-based learning process. At SD Negeri 3 Mendo Barat, there are still very few teaching materials owned by students, especially those based on AKM. This study aims to develop a companion mathematics module for preparing AKM for fifth-grade elementary school students that is valid, practical, and potentially affects learning outcomes. Development research using a 4-D model is used as a research technique. The research subjects were 22 students of class V SD Negeri 3 Mendo Barat, as many as 22 people. The results showed that the mathematics module was valid and practical—valid seen from the experts' assessment of the module. Experts consist of material, media, and language experts. Practicality is obtained from the results of student questionnaire analysis in a limited field test which shows a practicality percentage of 91.32 per cent. Based on the operational field test results, the average final score of students is 87.05, which indicates that student learning outcomes are in the very good category. The module can potentially affect student learning outcomes in the good category.